2021
DOI: 10.1021/acs.jpcc.1c07692
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Relationship between Zeolite Structure and MTO Product Distribution by Theoretical Study of the Reaction Mechanism

Abstract: Determination of the relative contributions of aromatic-based and alkene-based cycles in the MTO process is essential for understanding the reaction mechanism and estimating the product selectivity over various zeolites. However, it is a great challenge due to the high complexity of the reaction network. Thus, the olefin formation mechanisms are systematically investigated here by the density functional theory with van der Waals dispersive corrections over structurally different zeolites. It is shown that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…While our focus in this study has been on H-SSZ-13, we expect that the mechanism shown here is also the lowest energy mechanism for other zeotypes. Previous investigations have indeed shown that the original paring mechanism is unfavorable for H-ZSM-5 and H-SAPO-34 21 as well as H-BEA and H-ZSM-22, 58 thus strongly indicating that there has to be a more advantageous pathway for propylene formation with lower overall free energies.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…While our focus in this study has been on H-SSZ-13, we expect that the mechanism shown here is also the lowest energy mechanism for other zeotypes. Previous investigations have indeed shown that the original paring mechanism is unfavorable for H-ZSM-5 and H-SAPO-34 21 as well as H-BEA and H-ZSM-22, 58 thus strongly indicating that there has to be a more advantageous pathway for propylene formation with lower overall free energies.…”
Section: Resultsmentioning
confidence: 94%
“…Previous computational investigations on H-SAPO-34, 19,27,46 H-ZSM-5 21 and H-SSZ-13 49 have shown that the side-chain mechanism has a clear kinetic selectivity for ethylene. These investigations, however, have also shown that the rate-limiting step, the methylation of the side chain, is relatively high with computed activation free energies on the order of 190 kJ mol −1 or higher as determined by us for H-SSZ-13 57 and by others for H-SAPO-34, 49,58 H-ZSM-5, 58 H-BEA 58 and H-ZSM-22. 58 We note here that in our qualitative discussion of barrier heights, we always refer to Gibbs free energies and to the highest barrier encountered in the catalytic cycle relative to the lowest preceding intermediate, thus giving the largest 'span' as described nicely in the energetic span model.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations